Pengkayaan CaCl2 pada Nutrisi Hidroponik untuk Meningkatkan Hasil Tanaman Kailan (Brassica oleraceae L.) - M. Abror; Agus Miftakhurrohmat; Saiful Arifin (Jurnal Ilmu Pertanian Indonesia, 2023)
One highly sought-after vegetable is Kalian (Brassica oleraceae L.), valued for its exceptional nutritional content. The cultivation of kalian demands specialized attention. Hydroponic cultivation utilizing Calcium Chloride plays a pivotal role in fostering robust plant growth and resilience, particularly in urban settings. Calcium serves a multifaceted role: safeguarding against pests, enhancing fruit quality, and functioning as an antioxidant during storage. This research was conducted between October 2022 and February 2023, employing a single-factor Randomized Block Design (RBD) that was replicated three times. The study encompassed the following treatments: (i) Control with 0 ppm CaCl2, (ii) 550 ppm CaCl2 (P1), (iii) 650 ppm CaCl2 (P2), and (iv) 750 ppm CaCl2 (P3). The observed parameters encompassed plant height, leaf count, leaf area, fresh weight, and dry weight. The data underwent analysis via analysis of variance (ANOVA), followed by the Honest Significant Difference (HSD) test at the 5% significance level. The outcomes of the study unveiled substantial and statistically significant responses at the 7th, 14th, 21st, and 28th days after planting (HST) concerning the leaf count and wet weight variables. However, no statistically significant response was observed in relation to root length and leaf area measurements. Keywords: CaCl2, kailan, hydroponics, Ab Mix nutrition